Managing Change Toward Environmental Sustainability: A Conceptual Model in Small and Medium Enterprises. (June 2018) - Wiesner, Retha; Chadee, Doren; Best, Peter
This article aims to develop a model for managing change toward environmental sustainability (ES) within small and medium enterprises (SMEs) by investigating the main ES change management actions evident from the ES journeys of SME ES champions. Using in-depth face-to-face interviews, the article draws from the ES change management experiences of a sample of 12 ES champions from the SME sector, as well as secondary organization–specific data. A multicase design was adopted to develop the proposed model. A thematic content analysis identified 10 main change management actions along with a number of associated actions. The findings provide an empirically developed ES change management model and practical managerial ES change management guidelines to SMEs embarking on an ES journey.